Educational technologies for HIV prevention in black people: scope review - Nikaelly Pinheiro Mota; Jéssica Karen de Oliveira Maia; Wilson Jorge Correia Pinto Abreu; Marli Teresinha Gimeniz Galvão (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective: To map the educational technologies implemented for HIV prevention in black people. Method: Scope review, performed according to the recommendations of The Joanna Briggs Institute, in Medline/PubMed, Embase, LILACS, CINAHL, Scopus, Cochrane and PsycINFO databases, using the Preferred Reporting Items for Systematic reviews and Meta- Analyses extension for Scoping Reviews (PRISMA-ScR). Results: There were 14 studies published between 1999 and 2020. The main health impacts for black people involved a reduction in rates of unprotected sex, greater use of condoms, a decrease in risky behaviors, a minimization of the number of partners, a greater request for HIV testing and an increase in the use of Pre-exposure prophylaxis (PrEP). Conclusion: The educational technologies mapped were: workshops, courses, messages, dramatization, videos, application, pamphlet, media and radio campaigns, Facebook groups, website, computer programs and multimedia software.